The Asian Disease: Plausible Diagnoses, Possible Remedies - Martin Mayer (Levy Economics Institute of Bard College, 1998)
The Asian crisis is a textbook case of the "financial instability hypothesis" first expressed in 1966 by the late Hyman Minsky. Minsky's "hypothesis" was proposed to explain instability in a large, insulated, developed economy. Despite its intuitive appeal, it was not widely accepted among financial economists (Charles Kindleberger being a notable exception) because, they said, they could not find historical illustrations to fit the theory. The financial economist's machine runs smoothly in the best of all possible worlds. What makes trouble in the financial economist's world is the exogenous shock that affects everyone (war, oil prices) or government error (fiscal imbalance, monetary policy). "Financial distress," Barry Eichengreen and Richard Portes write in their study of sovereign debt rescheduling, "normally results from a real shock or bad policies." But Asia presents a cumulation of apparently rational decisions that are precisely those Minsky predicted.
Keywords: 330